2003
DOI: 10.3138/cmlr.60.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Bicultural Perspectives and Reader Response: Four American Readers Respond to Jean Fritz's Homesick

Abstract: The study of readers' responses to literature can help to make public the voices of bicultural children and young adults who experience life from a diversity of perspectives. This study explores the relationship between responses to literature and the complex world views of four bicultural students, three Asian American and one of Jewish and Eastern European descent. The focal literary work of the study was the cross-cultural text Homesick by Jean Fritz, a Newbery Honor book about the author's growing up in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Spears-Bunton (1990) observed that culturally conscious ethnic literature engaged students, both African American students and European American students. Using the case study approach, Leung (2003) worked with three Asian American students and one biracial (Jewish and Eastern European) student to explore factors involved in their reading of Jean Fritz"s Homesick (1982). The researcher concluded that personality traits, genre knowledge, knowledge of Chinese culture, and stage of ethnic identity development were the major factors bearing on the differences of the four readers" responses.…”
Section: Response To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Spears-Bunton (1990) observed that culturally conscious ethnic literature engaged students, both African American students and European American students. Using the case study approach, Leung (2003) worked with three Asian American students and one biracial (Jewish and Eastern European) student to explore factors involved in their reading of Jean Fritz"s Homesick (1982). The researcher concluded that personality traits, genre knowledge, knowledge of Chinese culture, and stage of ethnic identity development were the major factors bearing on the differences of the four readers" responses.…”
Section: Response To Literaturementioning
confidence: 99%
“…Most importantly, it creates opportunities for members from parallel cultures to become aware of alternative thoughts, to value their own culture, and to enhance the development of a positive identity (Enciso, 1994;Sims, 1983;Spears-Bunton, 1990). Leung (2003) also contends that cross-cultural readings serve as positive supports for minority students" ethnic identity development as well as a pool of diverse culture learning opportunities for mainstream students.…”
Section: Introductionmentioning
confidence: 99%
“…Without any opportunities to observe diverse cultures and heritages, these Anglo-American children may not be able to understand and respect differences and diversity. In the absence of culturallyauthentic representations, children may be exposed to racist and sexist attitudes, which can be perpetuated by books and other media (Leung, 2003). Over time, such pervasive images can distort their perceptions allowing stereotypes to become reality.…”
Section: Contemporary Realistic Fictionmentioning
confidence: 99%
“…Also, the current practice of using these books for holidays may promote exoticism (Willis-Rivera & Meeker, 2002) as Asian-Americans are placed outside the common historical narrative (Wills & Mehan, 1996). Thus, the effective use of multicultural children's literature, via employment of a critical lens, may better equip them to function in a pluralistic society (Leung, 2003).…”
Section: Contemporary Realistic Fictionmentioning
confidence: 99%
“…According to Banks (2005), members of the majority culture become accustomed to seeing their culture reflected and they start to believe that their values, beliefs, and expectations are universally accepted. In the absence of culturally different experiences, children may be exposed to stereotypes which are then perpetuated by books (Leung, 2003).…”
Section: )mentioning
confidence: 99%